The magic school bus hops home : a book about animal habitats - Relf, Patricia; Cole, Joanna; Stevenson, Nancy W. (New York : Scholastic, 1995)
Ms. Frizzle's class learns about the kinds of homes and living conditions that various animals require.
"Based on The magic school bus books written by Joanna Cole and illustrated by Bruce Degen"--T.p. verso.
"From an episode of the animated TV series produced by Scholastic Entertainment Inc."--T.p. verso.
3.0.
3.0
K-3
Keywords: Habitat (Ecology) -- Juvenile literature; Animals; Ecology; Habitat (Ecology); Animals; Ecology; Habitat (Ecology)